A metaheuristic-driven approach to fine-tune Deep Boltzmann Machines - Passos, Leandro Aparecido; Papa, Joao Paulo [UNESP] (Elsevier B.V., 2020)
Deep learning techniques, such as Deep Boltzmann Machines (DBMs), have received considerable attention over the past years due to the outstanding results concerning a variable range of domains. One of the main shortcomings of these techniques involves the choice of their hyperparameters, since they have a significant impact on the final results. This work addresses the issue of fine-tuning hyperparameters of Deep Boltzmann Machines using metaheuristic optimization techniques with different backgrounds, such as swarm intelligence, memoryand evolutionary-based approaches. Experiments conducted in three public datasets for binary image reconstruction showed that metaheuristic techniques can obtain reasonable results. (C) 2019 Elsevier B.V. All rights reserved.
Keywords: Deep Boltzmann Machine; Meta-heuristic optimization; Machine learning